2021
DOI: 10.1021/acs.est.1c02723
|View full text |Cite
|
Sign up to set email alerts
|

Organic Markers of Tire and Road Wear Particles in Sediments and Soils: Transformation Products of Major Antiozonants as Promising Candidates

Abstract: Tire and road wear particles (TRWPs) are one of the main sources of particulate traffic emissions, but measured data on TRWP contents in the environment are scarce. This study aims at identifying organic compounds suitable as quantitative markers for TRWPs by a tiered multistep selection process involving nontarget screening and subsequent identification by liquid-chromatography high-resolution mass spectrometry. Starting from several thousands of signals recorded in the extract of tire particles, the rigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 39 publications
8
79
1
1
Order By: Relevance
“…Similarly, MBT and BT concentrations decreased by 71 and 61% respectively, whereas HBT concentration increased by 71%. These results show that the artificial aging of CMTT led to chemical modification of the particles via oxidation processes, as has previously been described 41,44,45 . They also reveal the high degradability of 6PPD resulting in the production of several transformation products, among which 6PPD-Q.…”
Section: Cmtt Organic Chemical Compositionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, MBT and BT concentrations decreased by 71 and 61% respectively, whereas HBT concentration increased by 71%. These results show that the artificial aging of CMTT led to chemical modification of the particles via oxidation processes, as has previously been described 41,44,45 . They also reveal the high degradability of 6PPD resulting in the production of several transformation products, among which 6PPD-Q.…”
Section: Cmtt Organic Chemical Compositionsupporting
confidence: 83%
“…The presence of stable micelles was confirmed by dynamic light scattering, which revealed a high concentration of micelles with an average size of 154.8 nm and a zeta potential of -10 mV. Micelles-mediated solubilization has been demonstrated for bisphenol A 26 and PCBs 41 and is also likely responsible for the solubilization of hydrophobic organic compounds such as PAHs. These results are consistent with previous studies that showed greater solubilization of hydrophobic contaminants, such as PAHs and PCBs, from sediment in gut fluids compared to water, both in vitro and in vivo 56,57 but also from various types of microplastics 58,59 .…”
Section: 𝑏𝑖𝑜𝑎𝑐𝑐𝑒𝑠𝑠𝑖𝑏𝑙𝑒 𝑓𝑟𝑎𝑐𝑡𝑖𝑜𝑛 (%) = 𝑚 𝑓𝑓 𝑚 𝐶𝑀𝑇𝑇 * 100mentioning
confidence: 89%
See 1 more Smart Citation
“…Since tire wear has been considered a contributor to the release of PPDs and 6PPD-Q in multiple environment matrices, 8 , 12 , 33 , 34 we further investigate the occurrence of these novel PPD-Qs in the tire tread. As shown in Figure S4 and Table S6 , a considerable level of PPD-Qs could be detected in the tire treads (0.12–78,800 ng/g), implying that tire rubber may be a potential source for these PPD-Qs in the PM 2.5 samples.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study provided new evidence of multiple PPD-derived quinones in environmental media . These selected PPDs and their derived quinones have also been verified to be toxic and pervasive in the environment. In contrast to PPDs, NPAs and DPAs have rarely been investigated, and most have not yet entered the radar of toxicity or environmental studies. Generally, environmental PPDs, NPAs, and DPAs are considered to be linked to tire rubber. ,,, Comprehensive identifications of AAs, including PPDs, NPAs, and DPAs, as well as their significant sources other than tire rubber, are urgently needed to assess the overall risk.…”
Section: Introductionmentioning
confidence: 99%